LOCAL CULTURAL LITERACY AND ITS PROMOTION - Muljani, Retno; Sunarto, Emanuel (Sanata Dharma University, 2018)
As a place of conservation, research, education, and entertainment, a museum can support formal educational institutions to introduce kinds of literacy, including local cultural literacy. Local cultural literacy in this study referred to the knowledge of wayang ( = puppets) belonging to Museum Wayang Kekayon Yogyakarta (MWK). Visitors to MWK can learn the tangible and intangible aspects of wayang collections of MWK. As a preliminary study of a multi-year research, this study addressed two research questions: 1) what educational functions can be promoted through MWK collections? and 2) what criteria should promotional media have in order to promote MWK? The study implemented hermeneutic approach supported by theories of Semiotics, Discourse, Pragmatics, and Web Usability. Data were collected by browsing the Internet, conducting observations while visiting MWK, interviewing experts on museum, wayang, and semiotics and MWK educators. The findings of the study were 1) the identification of MWK educational functions to introduce cultural literacy and other relevant philosophical values, and 2) the CLEAR criteria of effective promotional media to promote cultural (wayang) literacy in the digital era. The study recommended that fun but meaningful activities should be conducted at MWK, and relevant resources and tools should be provided and used to support the activities.DOI: https://doi.org/10.24071/ijhs.2018.020104